2. CURRENT SITUATION OF PALLIATIVE CARE NEEDS OF CANCER PATIENTS RECEIVED INPATIENT TREATMENT AT HUE CENTRAL HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current situation and identify some factors related to the palliative care needs of cancer patients received inpatient treatment at Hue Central Hospital in 2023.Research methods: Cross-sectional descriptive study on 297 cancer patients aged 18 years and older are received inpatient treatment from 10/2023 to 12/2023 at Hue Central Hospital.Results: The average age of the study subjects was 56.47 ± 11.96, of which 57.6% were male. The proportion of patients in need of palliative care is 83.8%. The research subjects mainly need support for medical information and psychological (88.2%) and spiritual support (74.1%). The number of patients with low quality of life is 1.881 times higher need for palliative care than that of patients with high quality of life (95% CI = 0.979-3.631; p < 0.05).Conclusion: Cancer patients have a high need for palliative care. The patient’s current quality of life is related to the need for palliative care.
Keywords: Cancer; palliative care; quality of life